Trichomoniasis - Braga, Paulinisia de Carvalho; Santos, Mirelly de Oliveira Pedrosa; Silva, Maria Clara Teodoro; Alvarenga, Janaina Sousa Campos; Alvarenga, Ângela Cardoso de (Seven Editora, 2024)
Among the various known parasitic diseases, trichomoniasis draws attention because it is the most common non-viral sexually transmitted infection (STI) worldwide. According to the World Health Organization's (WHO) Global Health and Strategies Report on HIV, viral hepatitis and STIs, trichomoniasis, syphilis, gonorrhea and chlamydia together cause more than one million infections per day. DOI:https://doi.org/10.56238/sevened2024.001-039